Beetroot juice supplementation improves high-intensity intermittent type exercise performance in trained soccer players - Nyakayiru, J.; Jonvik, K. L.; Trommelen, J.; Pinckaers, P. J. M.; Senden, J. M.; van Loon, L. J. C.; Verdijk, L. B. (Nutrients, 2017)
It has been shown that nitrate supplementation can enhance endurance exercise performance. Recent work suggests that nitrate ingestion can also increase intermittent type exercise performance in recreational athletes. We hypothesized that six days of nitrate supplementation can improve high-intensity intermittent type exercise performance in trained soccer players. Thirty-two male soccer players (age: 23 ± 1 years, height: 181 ± 1 m, weight: 77 ± 1 kg, playing experience: 15.2 ± 0.5 years, playing in the first team of a 2nd or 3rd Dutch amateur league club) participated in this randomized, double-blind cross-over study. All subjects participated in two test days in which high-intensity intermittent running performance was assessed using the Yo-Yo IR1 test. Subjects ingested nitrate-rich (140 mL; ~800 mg nitrate/day; BR) or a nitrate-depleted beetroot juice (PLA) for six subsequent days, with at least eight days of wash-out between trials. The distance covered during the Yo-Yo IR1 was the primary outcome measure, while heart rate (HR) was measured continuously throughout the test, and a single blood and saliva sample were collected just prior to the test. Six days of BR ingestion increased plasma and salivary nitrate and nitrite concentrations in comparison to PLA (p < 0.001), and enhanced Yo-Yo IR1 test performance by 3.4 ± 1.3% (from 1574 ± 47 to 1623 ± 48 m; p = 0.027). Mean HR was lower in the BR (172 ± 2) vs. PLA trial (175 ± 2; p = 0.014). Six days of BR ingestion effectively improves high-intensity intermittent type exercise performance in trained soccer players